Some examples of critical analysis of legal texts from the viewpoint of John Austin’s performatives. (Herald of Journalism, 2016)
The paper reviews an example of using some characteristics of performatives, developed by John Austin, in analyzing legal texts. In our opinion, this approach could be useful in improving quality of the legal texts in general.
Keywords: law; legal; performatives; John Austin.